MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN METODE MIND MAPPING DALAM PEMBELAJARAN SEJARAH - Badrudin Badrudin; Weny Widyawati Bastaman; Usmaedi Usmaedi (KALA MANCA: JURNAL PENDIDIKAN SEJARAH, 2025)
History learning is sometimes a lesson that tends tobe difficult to learn because students are less interestedin studying history, this is because history learningtends to remember and study the past, so in this caseeducators or teachers must provide learning methodsthat tend to be short and concise. and clearly, of course,with fun, creative and innovative learning methods,which can be overcome with the mind mapping method